2017
DOI: 10.1371/journal.pone.0181470
|View full text |Cite
|
Sign up to set email alerts
|

Severe maternal morbidity in Zanzibar’s referral hospital: Measuring the impact of in-hospital care

Abstract: Objectiveto analyse the impact of in-hospital care on severe maternal morbidity using WHO’s near-miss approach in the low-resource, high mortality setting of Zanzibar’s referral hospital.SettingMnazi Mmoja Hospital, a tertiary care facility, in Zanzibar, Tanzania.MethodsWe identified all cases of morbidity and mortality in women admitted within 42 days after the end of pregnancy at Mnazi Mmoja Hospital in the period from April to October 2016. The severity of complications was classified using WHO’s near-miss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 21 publications
3
39
2
2
Order By: Relevance
“…The present rates of near‐miss using the WHO standard definition (1.79% and 4.00% in Tanzania and Uganda, respectively) compare well with other studies using the WHO standard definition . Higher rates have been described elsewhere in sub‐Saharan Africa, for example, in Mozambique where a high prevalence of HIV and a low uptake of prenatal care in the population might increase the incidence of maternal‐near miss .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present rates of near‐miss using the WHO standard definition (1.79% and 4.00% in Tanzania and Uganda, respectively) compare well with other studies using the WHO standard definition . Higher rates have been described elsewhere in sub‐Saharan Africa, for example, in Mozambique where a high prevalence of HIV and a low uptake of prenatal care in the population might increase the incidence of maternal‐near miss .…”
Section: Discussionsupporting
confidence: 81%
“…The mortality index (i.e., case‐fatality ratio) was found to range from 3% to 37% . A more recent review reported a median maternal near‐miss incidence of 2.4%, and other studies have reported low levels of near miss per 100 live births of 1.2 in Zanzibar, 2.5 in a rural hospital in Rwanda, 3.6 in district hospitals Rwanda, and 0.8 in Uganda (Supplementary Fig. S1).…”
Section: Introductionmentioning
confidence: 94%
“…A previous facility‐based survey in low‐ and middle‐income countries found that the likelihood of maternal near‐miss was eightfold and perinatal death threefold higher in a group of women with pre‐eclampsia than in a reference group without HDP . Although most cases are preventable, undiagnosed or suboptimally treated HDP is repeatedly reported in sub‐Saharan Africa . This violates human rights and is a key priority for safe motherhood …”
Section: Introductionmentioning
confidence: 99%
“…Lifesaving treatment includes induction and/or oxytocin augmentation of labor while stabilizing blood pressure (BP) and supporting vital organ functions . In high‐volume low‐resource hospitals, urgent intrapartum diagnosis, surveillance, and management of such complex diseases are challenging and need realistic practical guidance …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation